Analysis of Catalytic Aquathermolysis on the Physicochemical Properties of Colombian Heavy Crude Oils Using MALDI TOF Mass Spectrometry - Adan Leon-Bermudez; Dario Pena-Ballesteros; Emiliano Ariza; Nicolas Santos; Daniel Molina (Chemical Engineering Transactions)
Enhanced recovery methods play an important role in extracting crude oil from reservoirs using different processes. The catalytic aquathermolysis process is a promising technique due to the interaction of the catalyst, heavy oil fractions, and hydrogen (Water-Gas-Shift, WGS reactions). Fluid-fluid thermochemical interaction tests were performed in a batch reactor on three Colombian heavy crude oils (C1, C2, and C3) with iron naphthenate (100 ppm or mg/L, metal ion. Conditions at 270 °C and 800 psi during 66 h of reaction were set. To analyze the upgraded crude oils, physicochemical properties such as viscosity, density, and fraction distribution by simulated distillation (ASTM/D-7169) and SARA compositional analysis (saturated, aromatic, resins, asphaltenes) were evaluated. The results showed that heavy crude oils subjected to steam injection conditions presented an increase in viscosity and density compared to the original crude oils. Meanwhile, the viscosity and density reductions of the crude oils upgraded under catalytic aquathermolysis conditions ranged from 33.3 to 46.4 % and 0.22 to 1.71 %, respectively. With the information from the distillation curves, an increase between 3.5 and 7.8 % by weight in the content of light fractions (IBP - 370 °C) was evident. The increase in light fractions is mainly due to the conversion of vacuum residues (540°C+). On the other hand, the compositional analysis shows that the resin and asphaltenes fractions are reduced between 9.1 to 18.9 % by weight and between 14.8 to 25.9 % by weight. Saturates showed an increase in the range of 9.9 to 13.6 % by weight. Additionally, the results of MALDI-TOF mass spectrometry confirmed that the heavy fractions and asphaltenes tend to form species with lower molecular weight. Finally, the variation in the physicochemical properties of heavy crude oils shows that the thermochemical method is a valuable and complementary tool in thermal recovery.